AB0459 Remission rate of tocilizumab in controlled trials and observational studies: systematic review of rheumatoid arthritis. (12th June 2018) - Kucuksahin, O.; Kılıç, L.; Aşlar, Z.; Bes, C.; Yazısız, V.; Yazıcı, A.; Solmaz, D.; Kaşifoğlu, T.; Kalyoncu, U.
Abstract : Background: In concept, the state of remission constitutes a clinical condition in which no active disease is present. Target of rheumatoid arthritis (RA) is achieve to remission. Tocilizumab (TOC) is a humanised monoclonal antibody that binds to the interleukin-6 receptor Objectives: The aim of this study was to assess the remission rate of TOC for the treatment of RA patients in randomised controlled trials (RCTs) and longitudinal observational studies (LOS). Methods: In January 2017, a systematic Review (SR) was performed in PUBMED MEDLINE. Publications were identified using the MeSH terms: (''rheumatoid arthritis and Tocilizumab'') with a limitation to ''humans'', ''all adults: 19+years'', ''English'' and ''clinical trials''. All available studies describing the retention rate of TOC were recruited to SR. Retention rate of TOC were calculated according to route (SC or IV), dosage (4 mg/kg vs 8 mg/kg), monotherapy or combination with methotrexate. Of the 662 publications identified by the literature search, 42 were recruited in the analysis. Retention rates of TOC at 12–16 weeks, 24–32 weeks, 48–52 weeks, 2. Years, 3. Years and 5. years were analysed. Open label extension period of RCTs included to LOS. The causes of withdraw of TOC were recorded as inefficacy, adverse event, and others. Results: Of the 34 studies, 13 (38%) were RCTs and 21 (62%) were LOSs. Totally 12 043 patients (9834 (81%) female) were pooled to analysis that 6190 patients (51%) were from RCTs. The mean age was 53 years and mean disease duration was 9 years. Seropositivty was 73.6% for rheumatoid factor and 72.2% for ACPA. Overall, 5493 (54.6%) of patients were biologic-naïve. TOC was used as monotherapy (2469/6077, 35.4%), or concomitant with methotrexate (8037/11429, 70.3%). Available baseline DAS-28 score, CDAI, SDAI, and HAQ-DI score were 6.2, 32.1, 33.3, and 1.49 respectively. Remission rate of TOC according to study type were shown in table 1. Conclusions: These systematic literature results show that treatment with of TOC has a high likelihood of inducing a clinically important benefit in terms of different remission criteria. Remission achieved both RCTs and real life results Moreover, remission rate of TOC in LOSs was comparable with other biologic DMARDs, as well. Disclosure of Interest: None declared